Shade reproduction and the ability of lithium disilicate ceramics to mask dark substrates - Maryam Iravani; Sayna Shamszadeh; Narges Panahandeh; Seyedeh Mahsa Sheikh-Al-Eslamian; Hassan Torabzadeh (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to evaluate the ability of lithium disilicate ceramics to reproduce the A2 shade and to mask A4 substrates.Materials and MethodsTwenty-four discs (8 mm in diameter, shade A2) of high translucency (groups 1–3) and low translucency (groups 4–6) of IPS e.max ceramic with different thicknesses (0.5, 0.75, and 1 mm) were fabricated as monolithic structures. In addition, discs of medium opacity (group 7–8) with different core/veneer combinations (0.3 mm/0.7 mm and 0.5 mm/0.5 mm) were fabricated as bilayer structures. Specimens were superimposed on an A4 substrate (complex). The color changes of the complex were measured using a spectrophotometer on a black background, and the ΔE values of the complex were compared with either the A4 substrate or the A2 shade tab. One-way analysis of variance, the Tukey honest significant difference test, and the Fisher test were used to analyze the data (p < 0.05).ResultsSignificant between-group differences were found for comparisons to both the A4 substrate and the A2 shade (p < 0.05). When compared with the A4 substrate, the ΔE values in all groups were in the non-acceptable range. When compared with the A2 shade, the ΔE values in all groups, except groups 2 and 3, were in the clinically acceptable range.ConclusionsAll translucencies and thicknesses masked the underlying dark substrate. However, the low-translucency IPS e.max Press better reproduced the A2 shade.